If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x/3+10=12
We move all terms to the left:
-x/3+10-(12)=0
We add all the numbers together, and all the variables
-x/3-2=0
We multiply all the terms by the denominator
-x-2*3=0
We add all the numbers together, and all the variables
-1x-6=0
We move all terms containing x to the left, all other terms to the right
-x=6
x=6/-1
x=-6
| 4n+30=30 | | 15=0.5+2x+10 | | -2x(x-3)=12 | | 4(2m-5)-3m=20m+5m | | 2m-3/5-m/3=-6/5 | | 6x-4+10x-18=15x-13 | | a+4.8=9.2 | | 4,5y=16.65 | | -14k=6k=8 | | (12-2u=9u+45 | | {25+15+18+p}{4}=20 | | 5*x+7=7+9x | | 1−2r+3r=−1 | | u/3-8=21 | | 12x=7/4 | | 5+4(x-1)=42-6x | | 2n-4-2=12 | | -16+46=-5(x+1) | | -7v+v=18 | | 2/7b=-20 | | 8(5+5n)=160 | | 6x+x-4=16 | | 9t−–3=57 | | 3³x-²=81 | | 6=2n-8;n=5 | | 3x+25=-2x* | | ½(e-3)-2=2e+1 | | 8+n=13;n= | | 15=1/2+2x+10 | | -9g=-27 | | 1/3(3j+4)=-2j+5 | | -c/9+7=14 |